Monitoring results of wild boar (Sus scrofa) in The Netherlands: analyses of serological results and the first identification of Brucella suis biovar 2. Issue 1 (1st January 2020) - van Tulden, Peter; Gonzales, Jose L.; Kroese, Michiel; Engelsma, Marc; de Zwart, Frido; Szot, Dorota; Bisselink, Yvette; van Setten, Marga; Koene, Miriam; Willemsen, Peter; Roest, Hendrik-Jan; van der Giessen, Joke
ABSTRACT: In Europe, wild boar populations pose an increasing risk for livestock and humans due to the transmission of animal and zoonotic infectious diseases, such as African swine fever and brucellosis. Brucella suis is widespread among wild boar in many European countries. In The Netherlands the prevalence of B. suis among wild boar has not been investigated so far, despite the high number of pig farms and the growing wild boar population. The Netherlands has a Brucella -free status for the livestock species. The objective of this study is to investigate the presence and distribution of B. suis in wild boars in The Netherlands and to assess the value of the different laboratory tests available for testing wild boars. A total of 2057 sera and 180 tonsils of wild boar were collected between 2010 and 2015. The sera were tested for Brucella antibodies and the tonsils were tested for Brucella spp. B. suis biovar 2 was detected by MLVA/MLST and culture in wild boar from the province of Limburg, while seropositive wild boar were obtained from the provinces of Limburg, Noord Brabant and Gelderland suggesting the northwards spread of B. suis biovar 2. In this paper, we describe the first isolation of B. suis biovar 2 in wild boar in The Netherlands.